2021
DOI: 10.1177/17470218211048108
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional and situational predictors of coping with violated achievement expectations

Abstract: Most students experience expectation violations during their academic career, such as unexpected failed tests. However, contradictory evidence does not always result in expectation change (accommodation). Expectations often persist through stronger efforts to fulfil the expectation (assimilation) or ignoring the discrepancy (immunization). Our study addresses possible situational and dispositional predictors that may be decisive influences on the use of the three coping strategies. We conducted an experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…Therefore, it seems reasonable that both predictors interact with each other in addition to their main effect on coping with expectation violations. Both predictors revealed significant but partly surprising results in a previous study (Henss and Pinquart, 2022) and will therefore be further explored in a similar study design. The following research questions were addressed: First, does a negative valence of expectation violation lead to stronger assimilation (similar to our previous study; Henss and Pinquart, 2022) as well as stronger immunization and weaker accommodation compared to positive valence of expectation violation?…”
Section: The Present Studymentioning
confidence: 74%
See 4 more Smart Citations
“…Therefore, it seems reasonable that both predictors interact with each other in addition to their main effect on coping with expectation violations. Both predictors revealed significant but partly surprising results in a previous study (Henss and Pinquart, 2022) and will therefore be further explored in a similar study design. The following research questions were addressed: First, does a negative valence of expectation violation lead to stronger assimilation (similar to our previous study; Henss and Pinquart, 2022) as well as stronger immunization and weaker accommodation compared to positive valence of expectation violation?…”
Section: The Present Studymentioning
confidence: 74%
“…Both predictors revealed significant but partly surprising results in a previous study (Henss and Pinquart, 2022) and will therefore be further explored in a similar study design. The following research questions were addressed: First, does a negative valence of expectation violation lead to stronger assimilation (similar to our previous study; Henss and Pinquart, 2022) as well as stronger immunization and weaker accommodation compared to positive valence of expectation violation? Second, does higher NCC predict stronger accommodation and assimilation (similar to the study by Henss and Pinquart, 2022) and stronger immunization (as found by Schrackmann and Oswald, 2014)?…”
Section: The Present Studymentioning
confidence: 74%
See 3 more Smart Citations